2021
DOI: 10.1111/1462-2920.15700
|View full text |Cite
|
Sign up to set email alerts
|

The bacterium Pseudomonas protegens antagonizes the microalga Chlamydomonas reinhardtii using a blend of toxins

Abstract: The unicellular alga Chlamydomonas reinhardtii and the bacterium Pseudomonas protegens serve as a model to study the interactions between photosynthetic and heterotrophic microorganisms. P. protegens secretes the cyclic lipopeptide orfamide A that interferes with cytosolic Ca 2+ homeostasis in C. reinhardtii resulting in deflagellation of the algal cells. Here, we studied the roles of additional secondary metabolites secreted by P. protegens using individual compounds and co-cultivation of algae with bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 54 publications
(104 reference statements)
0
23
0
Order By: Relevance
“…This is exemplified by the genomic analysis of algicidal bacterium Brevibacillus laterosporus Bl-zj, which included a number of genes putatively involved in algicidal activity, including virulence factors, proteases and antibiotic resistance genes ( Zhang et al, 2021a ). While a full description of algicidal compounds that have been identified is beyond the scope of this review, it is worthy to note the growing realization that a number of algicidal chemicals produced by bacteria act additively or synergistically ( Harvey et al, 2016 ; Wang and Seyedsayamdost, 2017 ; Zhuang et al, 2018 ; Ternon et al, 2019 ; Jeong and Son, 2021 ; Rose et al, 2021 ). These groups of chemicals may act together to overwhelm one physiological target, and/or affect multiple systems simultaneously.…”
Section: Algicidal Interactionsmentioning
confidence: 99%
“…This is exemplified by the genomic analysis of algicidal bacterium Brevibacillus laterosporus Bl-zj, which included a number of genes putatively involved in algicidal activity, including virulence factors, proteases and antibiotic resistance genes ( Zhang et al, 2021a ). While a full description of algicidal compounds that have been identified is beyond the scope of this review, it is worthy to note the growing realization that a number of algicidal chemicals produced by bacteria act additively or synergistically ( Harvey et al, 2016 ; Wang and Seyedsayamdost, 2017 ; Zhuang et al, 2018 ; Ternon et al, 2019 ; Jeong and Son, 2021 ; Rose et al, 2021 ). These groups of chemicals may act together to overwhelm one physiological target, and/or affect multiple systems simultaneously.…”
Section: Algicidal Interactionsmentioning
confidence: 99%
“…To compare the biological response of synthetic CLPs 2 and 3 to isolated orfamide A in C. reinhardtii, we used the transgenic AEQ34 cell line that expresses apo-aequorin for measuring cytosolic Ca 2 + levels (for details see Supporting Information). [9,10] CLP 3 showed identical characteristics to the natural product, with a rapidly occurring initial Ca 2 + release signal and a secondary Ca 2 + -release that persisted over several minutes. These data additionally confirmed that compound 3 has the correct structure of orfamide A. CLP 2, which differs from CLP 3 only in the configuration of two residues, showed a distinct Ca 2 + signature, where the initial signal was strongly reduced and the secondary release was absent (Figure 5).…”
Section: Reagents and Conditionsmentioning
confidence: 83%
“…To compare the biological response of synthetic CLPs 2 and 3 to isolated orfamide A in C. reinhardtii , we used the transgenic AEQ34 cell line that expresses apo‐aequorin for measuring cytosolic Ca 2+ levels (for details see Supporting Information) [9,10] . CLP 3 showed identical characteristics to the natural product, with a rapidly occurring initial Ca 2+ release signal and a secondary Ca 2+ ‐release that persisted over several minutes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations